ANALISIS SKEMA INSENTIF PAJAK DALAM RANGKA NET ZERO EMISSION SEKTOR ENERGI DI INDONESIA - Haptari, Vissia Dewi (JURNAL PAJAK INDONESIA, 2023)
The achievement of net zero emission is a government commitment that not only relies on the government, but also the role of the business sector and society. In achieving net zero emissions, the government focuses on the development of renewable energy and the carbonization movement. In order to attract investors to develop renewable energy, tax incentives alone are not enough, but also require increasing ease of business as a major factor in investing. Tax incentives are directed to two groups, namely taxpayers who invest or carry out the construction and development of renewable energy projects and taxpayers who carry out decarbonization activities by utilizing or using renewable energy